Influences of H2SO4 and NaCl Concentrations on Stress Corrosion Cracking of AISI 304 Stainless Steel - Nur Azhani, Abd Razak; Asmara, Y. P.; Mohamad Khairuazlan, Kamaruzaman (Scientific.net, 2014)
This paper presents the influence of H2SO4 and NaCl concentrations on the corrosion mode of AISI 304 stainless steel in H2SO4-NaCl aqueous solutions. Immersion test was conducted at room temperature using U-bend specimens. The specimens in annealed and sensitized conditions were immersed in aqueous solutions containing H2SO4 concentration in the range of 0 to 3.0 kmol/m3 with 1.5 kmol/m3 interval, and NaCl concentration in the range of 0.5 to 2.0 kmol/m3 with 0.5 kmol/m3 interval. Results showed that, specimens in sensitized condition have a higher mass loss and higher corrosion rate. In addition, the experimental result also indicates that the two solutes have synergistic effect on corrosion mode of the material that is stress corrosion cracking (SCC) and general corrosion, which occur within a specific range of concentration. SCC region became smaller as the H2SO4 and NaCl concentration increased. However, the occurrence of SCC was high when sensitization treatment was subjected to the specimens. The appearance of surface damage and crack morphology were revealed by using scanning electron microscopy (SEM).